Digital media, territory, and diaspora: the shape-shifting spaces of Eritrean politics. Issue 1 (2nd January 2020) - Bernal, Victoria
ABSTRACT: Nations are generally understood to be territorial while the internet is commonly thought of as extraterritorial. The political activities of Eritreans in diaspora help to complicate both those assumptions. Exploring the diverse and shifting ways that Eritreans in diaspora have used websites to participate in national politics from outside the country sheds light on the dynamics of the space of cyberspace and its significance for politics. With regard to territory, I suggest that the significant feature of the internet is not its extraterritoriality but rather that the space of cyberspace is ambiguous and elastic, allowing it to support diverse constructions, alternative imaginaries, and multiple forms of territoriality, virtuality, and extraterritoriality. Diasporas, much like cyberspace, are altering the meaning of territorial locations and borders, disrupting prior configurations of society and territory, and making possible new spatializations of politics. Eritreans in diaspora are experimenting online in ways that show the internet cannot be defined by its quality of extraterritoriality or by its relation to territory in fixed terms. Their activities suggest ways of thinking about the internet in terms of various and shifting permutations of cyberspatial and territorial relations, that are always both grounded and virtual.